Beyond 'Liberals' and 'Conservatives': Complexity in Ideology, Moral Intuitions, and Worldview Among Swedish Voters. Issue 3 (26th March 2020) - Nilsson, Artur; Montgomery, Henry; Dimdins, Girts; Sandgren, Maria; Erlandsson, Arvid; Taleny, Adrian
Abstract: This research investigated the congruence between the ideologies of political parties and the ideological preferences ( N  = 1515), moral intuitions ( N  = 1048), and political values and worldviews ( N  = 1345) of diverse samples of Swedish adults who voted or intended to vote for the parties. Logistic regression analyses yielded support for a series of hypotheses about variations in ideology beyond the left–right division. With respect to social ideology, resistance to change and binding moral intuitions predicted stronger preference for a social democratic (vs. progressive) party on the left and weaker preference for a social liberal (vs. social conservative or liberal‐conservative) party on the right. With respect to political values and broader worldviews, normativism and low acceptance of immigrants predicted the strongest preference for a nationalist party, while environmentalism predicted the strongest preference for a green party. The effects were generally strong and robust when we controlled for left–right self‐placements, economic ideology, and demographic characteristics. These results show that personality variation in the ideological domain is not reducible to the simplistic contrast between 'liberals' and 'conservatives', which ignores differences between progressive and non‐progressive leftists, economic and green progressives, social liberal and conservative rightists, and nationalist and non‐nationalist conservatives.